Kinetika dan Mekanisme Pelindian Limonit : Pengaruh Waktu dan Temperatur [Kinetics and Mechanism of Limonite Nickel Ore Dissolution : Effect of Time and Temperature] - Eni Febriana; Agung Tristiyan; Wahyu Mayangsari; Agus Budi Prasetyo (Metalurgi, 2018)
Leaching by using sulfuric acid for nickel extraction of Halmahera limonite ore was investigated. Characterization of the ore was conducted by XRD (x-ray diffraction), XRF (x-ray flourescence), and SEM (scanning electron microscopy). The leaching was carried out under atmospheric pressure. Kinetic of leaching was studied by following the shrinking core model. The effect of temperatur and time were studied at various temperatures of 30, 50, and 90 °C with leaching time up to 480 minutes. A maximum 95% Ni extraction value was obtained for 480 min leaching at 90 °C from -150+200 mesh of limonitic nickel ore, with a concentration of H2SO4 of 1 M and a 2.5% ore / liquid ratio. The results show that the leaching rate of Ni is generally controlled by diffusion through the product layer with activation energy for the leaching of 78.0 kJ/mol. The leachingmechanism of limonite ores was identified from the result of residual leaching XRD graph. With increasing temperatur and the longer of leaching time, % extraction of Ni was increased. This condition followed by increasing of the quartz peak’s intensity at 2 = 26 °. AbstrakPelindian dengan pelarut asam sulfat untuk ekstraksi nikel dari bijih limonit Halmahera telah diteliti. Karakterisasi bijih menggunakan XRD, XRF, dan SEM. Pelindian dilakukan pada tekanan atmosfir. Kinetika pelarutan dipelajari dengan mengikuti model Shrinking Core. Pengaruh temperatur dan waktu yang dipelajari yaitu pada temperatur 30oC, 50oC, dan 90oC dengan waktu pelindian hingga 480 menit. Nilai % ekstraksi Ni maksimum sebesar 95,9% diperoleh pada pelindian selama 480 menit pada temperatur 90oC. Hasil analisis menunjukkan bahwa laju pelarutan Ni secara umum dikendalikan oleh difusi. Energi aktivasi untuk pelindian sebesar 83,8 kJ/mol. Mekanisme pelarutan bijih limonit diidentifikasikan dari grafik XRD residu hasil pelindian. Semakin tinggi temperatur dan semakin lama waktu pelindian memperbesar % ekstraksi Ni diikuti dengan meningkatnya intensitas puncak kuarsa.